Introduction: The "Clash of Civilizations" and Relations between the West and the Muslim World - Haynes, Jeffrey (The review of faith & international affairs, 2019)
The spring 2019 issue of The Review of Faith & International Affairs brings together nine scholars to examine various issues contained within a general research question: does Samuel Huntington's 'clash of civilizations' paradigm help explain current Western governments' responses to Muslim migration and related security issues? The contributors seek to explicate both theoretical and empirical examinations of Huntington's 'clash of civilizations' thesis in relation to the West. Our initial premise is that in the quarter century since Huntington first aired his controversial framework, inter-civilizational 'clash' and 'dialogue' have become mainstream issues both in international relations and in many Western countries' domestic concerns.